Anisotropy in the Angular Momentum Vector of Galaxies in the SDSSCGB 73384 - Malla, Janak Ratna; Saurer, Walter; Aryal, Binil (Academia Research Journal, 2025)
This work studied the angular momentum vectors of 1,017 galaxies in the SDSS CGB73384 Supercluster. This paper finds the preferred alignments of spin vectors of galaxies in the SDSS CGB73384 Supercluster. Using three statistical tests: Chi-square, Auto-correlation and the Fourier test for whether angular momentum vector of galaxies isotropy or anisotropy. To check our results to the different galaxy evolution models namely Hierarchy, Primordial vorticity and Pancake model. Finally, we observed that the spin vector orientations of galaxies are parallel with respect to the equatorial co-ordinate system in the SDSS CGB73384 Supercluster, supporting Pancake model.